Subpicosecond metamagnetic phase transition in FeRh driven by non-equilibrium electron dynamics - Federico Pressacco (Nature Portfolio, 2021)
In FeRh, it is possible to optically drive a phase transition between ferromagnetic (FM) and anti-ferromagnetic (AFM) ordering. Here, using a combination of photoelectron spectroscopy and ab-initio calculations, the authors demonstrate the existence of a transient intermediate phase, explaining the delayed appearance of the FM phase.